The global impact of the U.S. inflation reduction act: Evidence from an international expert survey - Klaus Gründler; Philipp Heil; Niklas Potrafke; Timo Wochner (CESifo GmbH, 2023)
The US Inflation Reduction Act (IRA) promotes renewable energy and contributes to climate protection, but also offers generous tax credits and subsidies to incentivize production in the United States. While the planned generosity of the program has sparked an intense debate about potential negative spillover effects on the global economy, little is known about the quantity of potential adverse effects. We conduct a large-scale international survey among leading economic experts worldwide to quantify the effect of the US Inflation reduction act on the global economy. On a global scale, experts are little concerned about negative effects of the IRA on their domestic economy, estimating both the impact on national output and the risk of business outflows to be low. However, we uncover large heterogeneity in the potential impact of the IRA across countries and regions. In Europe, particularly in France and Germany, economic experts are highly concerned about the IRA and expect a significant effect of the IRA on the domestic economy. In terms of economic policy reactions, roughly 41% of the respondents support economic countermeasures. We elicit experts' views about policy measures in open-ended text questions to prevent any priming of the respondents. The respondents propose active industrial policy, including subsidies, but also advocate for increased investment in infrastructure and green sectors. The call for subsidies is particularly strong in Europe.
Keywords: 330; Finanzpolitik; Förderung erneuerbarer Energien; Klimaschutz; USA; Wirkungsanalyse; Politikberatung; Experten; Europa; Welt